Feasibility of stereotactic radiotherapy using a 1.5 T MR-linac: Multi-fraction treatment of pelvic lymph node oligometastases. (May 2019) - Werensteijn-Honingh, Anita M.; Kroon, Petra S.; Winkel, Dennis; Aalbers, Ellart M.; van Asselen, Bram; Bol, Gijsbert H.; Brown, Kevin J.; Eppinga, Wietse S.C.; van Es, Corine A.; Glitzner, Markus; de Groot-van Breugel, Eline N.; Hackett, Sara L.; et al.
Highlights: 5 patients with pelvic lymph node metastases received SBRT using a 1.5 T MR-linac. Session time was <60 min for all 25 treatment fractions. All quality assurance tests were passed (dose calculations & film measurements). Abstract: Online adaptive radiotherapy using the 1.5 Tesla MR-linac is feasible for SBRT (5 × 7 Gy) of pelvic lymph node oligometastases. The workflow allows full online planning based on daily anatomy. Session duration is less than 60 min. Quality assurance tests, including independent 3D dose calculations and film measurements were passed.